Instilling Children's Character Education Through Tutoring in Krandegan Hamlet Sukomakmur Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The problem of the deteriorating character of the Indonesian nation is a major concern in facing the threat of globalization and foreign cultural influences. This study aims to evaluate the effectiveness of character education, especially in tutoring activities, in dealing with this problem. With the Community Asset-Based Development (ABCD) approach, service activities will be carried out in Krandegan Village, Magelang Regency, from July 20 to September 5, 2023. This research highlights the importance of character education in shaping future generations who have positive values. The results showed that tutoring that integrates character education and IT introduction for grade 5 students can instill positive character values, despite being faced with challenges such as student indifference and lack of initiative. This study makes an important contribution to understanding national character challenges and offers practical insights for effective character education strategies in Indonesia